The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/jclp.20523
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists who abstain from personal therapy: do they practice what they preach?

Abstract: The authors examined the attitudes and reasons of 119 American psychologists, counselors, and clinical social workers who had never sought personal therapy. Nontherapy seekers, compared to therapy seekers, expressed less-positive attitudes toward its value as a prerequisite for clinical work and for ongoing professional development. Women, men, and members of all three professions were equally likely to have sought therapy, but cognitive-behavioral therapists and academics were significantly less likely to do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…It is evident from this study that most therapists in English-speaking countries do indeed ''practice what they preach'' (Norcross et al, 2008), as therapists clearly also do in many European countries . Substantial majorities were found across professional disciplines, theoretical orientations, experience levels, age, and gender.…”
Section: Clinical Practices and Summarymentioning
confidence: 69%
See 1 more Smart Citation
“…It is evident from this study that most therapists in English-speaking countries do indeed ''practice what they preach'' (Norcross et al, 2008), as therapists clearly also do in many European countries . Substantial majorities were found across professional disciplines, theoretical orientations, experience levels, age, and gender.…”
Section: Clinical Practices and Summarymentioning
confidence: 69%
“…Seeking therapy was associated with year in the training program, believing that therapy was necessary to training, having positive attitudes towards help seeking, and concerns about confidentiality. However, a proportion of therapists choose not to undertake personal therapy, citing sufficient social support and a belief in their own understanding of coping strategies for the maintenance of their well-being (Norcross, Bike, Evans, & Schatz, 2008). (Wiseman & Shefler, 2001).…”
Section: Perceived Importancementioning
confidence: 99%
“…In an effort to train ethical and well‐adjusted counselors, it is important that we understand any potential barriers that prevent mental health professionals and trainees from seeking therapy, or whether these individuals differ from their therapy‐seeking counterparts in any meaningful way. To this end, Norcross, Bike, Evans, and Schatz () surveyed 119 therapy‐declining American psychologists, counselors, and social workers in an effort to determine the existence of perceived barriers to therapists seeking their own therapy. The authors also examined the participants' attitudes about personal therapy.…”
Section: Applicability To Counselor Training Programsmentioning
confidence: 99%
“…Importantly, several earlier studies (Deutsch, ; Gilroy, Carroll, & Murra, ; Norman & Rosvall, ) did not list many of these reasons as possible responses. Therefore, until the research by Norcross et al (), it appeared that issues of cost or concerns about confidentiality were the most prominent barriers to clinicians seeking personal therapy. Indeed, the authors also reported that only 31% of therapy decliners indicated that they were likely to ever seek therapy.…”
Section: Applicability To Counselor Training Programsmentioning
confidence: 99%
See 1 more Smart Citation